Variations in the ratio between von Willebrand factor and its cleaving protease during systemic inflammation and association with severity and prognosis of organ failure - Claus, Ralf A.; Bockmeyer, Clemens L.; Budde, Ulrich; Kentouche, Karim; Sossdorf, Maik; Hilberg, Thomas; Schneppenheim, Reinhart; Reinhart, Konrad; Bauer, Michael; Brunkhorst, Frank M.; Lösche, Wolfgang (Thrombosis and Haemostasis, 2009)
Von Willebrand factor (VWF) and related parameters as well as the protease activity regulating its biological activity were measured in plasma of healthy controls and patients with different cause and severity of systemic inflammation to examine the efficacy of the measures to detect highly prothrombotic states including thrombotic microangiopathy (TMA), one of the sequelae of sepsis. Plasma levels of VWF increased with increasing severity of systemic inflammation, probably due to activation of the endothelium. In parallel, the proteolytic activity of VWF inactivating protease, ADAMTS13, stepwise declined with the severity of inflammation, emphasizing the role of VWF-triggered platelet aggregation on the endothelium subsequently followed by development of TMA. As a consequence, the ratio of VWF antigen level and ADAMTS13 activity was significantly higher in patients with inflammation and sepsis, suggesting that this ratio might be more useful for the diagnosis of highly prothrombotic states including TMA than VWF multimer analysis alone. These findings suggest that ADAMTS13, VWF and related parameters, even in a combined approach, might be useful for the diagnosis and the therapeutic monitoring of patients with sepsis associated thrombotic microangiopathy.
Keywords: ADAMTS13; sepsis; systemic inflammation; organ failure; platelets; thrombotic microangiopathy; TMA-index